2014
DOI: 10.1007/s00431-014-2297-3
|View full text |Cite
|
Sign up to set email alerts
|

Voiding urosonography with second-generation ultrasound contrast versus micturating cystourethrography in the diagnosis of vesicoureteric reflux

Abstract: Vesicoureteric reflux has been associated with paediatric urinary tract infection. Fluoroscopic micturating cystourethrography (MCU) has been the gold standard of diagnostic test for decades; however, it has been criticized owing to its lower detection rate and radiation dose to children. Therefore, new radiation-free reflux imaging modalities have been developed, in which ultrasound-based contrast-enhanced voiding urosonography (ceVUS) is a good example. However, ultrasonography has been considered as an oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 29 publications
5
24
0
1
Order By: Relevance
“…Vesicoureteral reflux is identified in 30% to 50% of all children, boys and girls, presenting with a first urinary tract infection11 and in 27.4% of siblings of patients with documented VUR 12. Although traditionally VUR is investigated with fluoroscopic VCUG, limited sensitivity due to intermittent fluoroscopy and concerns about childhood radiation exposure have led to the search for an effective, radiation‐free alternative to VCUG 13…”
Section: Discussionmentioning
confidence: 99%
“…Vesicoureteral reflux is identified in 30% to 50% of all children, boys and girls, presenting with a first urinary tract infection11 and in 27.4% of siblings of patients with documented VUR 12. Although traditionally VUR is investigated with fluoroscopic VCUG, limited sensitivity due to intermittent fluoroscopy and concerns about childhood radiation exposure have led to the search for an effective, radiation‐free alternative to VCUG 13…”
Section: Discussionmentioning
confidence: 99%
“…As the VUR is a real-time radiation free technique and the switch from one kidney to contralateral is extremely rapid, the continuous exploration without any pauses captures a higher number of refluxes in both sides. Many authors consider that the VUS with a second-generation contrast agent is superior to conventional fluoroscopic cystography in the detection and grading of VUR [3,5,13]. In addition, the absence of major side effects and low incidence of minor side effects such as dysuria, -not related to the contrast agent, but rather to bladder catheterization-are definite advantages [14].…”
Section: Discussionmentioning
confidence: 99%
“…Combined use with tissue harmonic imaging that has a high sensitivity for contrast agent [1,2] has improved the diagnostic accuracy of this method, which is nearly 100% in the most recent case studies [3]. VUS, as the standardized technique, is used to acquire information during the bladder filling and voiding phase [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The second generation of ultrasound contrast agents (UCA) and higher quality ultrasound machines, with contrast-specific software technology, have allowed the application of ceVUS without ionizing radiation (15). ceVUS has become a routine method in the diagnosis of VUR in many European centres, because in recent years there is higher awareness of the potential harmful effects of exposure to ionizing radiation in diagnostic imaging procedures in children (15)(16)(17)(18)(19)(20)(21)(22)(23). Kis et al (25) reported ceVUS to be more sensitive than VCUG since it is a real time imaging method, allowing prolonged, continuous scanning, and thus has the potential to detect intermittent VUR (24).…”
Section: Contrast-enhanced Voiding Urosonographymentioning
confidence: 99%